Breast cancer and Flammer syndrome: any symptoms in common for prediction, prevention and personalised medical approach? - Zubor, Pavol; Gondova, Alexandra; Polivka, Jiri; Kasajova, Petra; Konieczka, Katarzyna; Danko, Jan; Golubnitschaja, Olga (The EPMA journal, 2017)
An epidemic scale of the breast cancer (BC) prevalence is actually recognised as the reality of the early twenty-first century. Particularly alarming is that the sporadic BC (about 90% of all patients) creates currently unpredictable subpopulations in terms of disease predisposition, development and progression. Despite broad discussions run since years in BC area, no any plausible approach has been suggested so far to get the overall situation better controlled in the populations. Here, we present highly innovative concepts considering investigation of specific syndromes and symptoms underestimated till now in relationship with BC predisposition and development. Consequently, the purpose of our pilot project was to evaluate the prevalence of Flammer Syndrome (FS) in BC patient cohort. The results achieved here support the main hypothesis of the project clearly demonstrating the tendency of BC patients to the increased prevalence of FS symptoms compared to the disease-free individuals. Our study strongly indicates the relevance of FS symptoms for BC pathology such as feeling inadequately cold, deficient thermoregulation, altered sensitivity to different stimuli, potential dehydration, altered sleep patterns, tendency towards headache, migraine attacks and dizziness. Moreover, the symptoms' appearance is specifically linked to the individual BC subtypes. Potential mechanisms interconnecting FS with BC pathology are discussed.
Keywords: Cardiovascular component; Thermoregulation; Sense regulation; Drug sensitivity; Pain; Systemic hypoxia; Patient stratification; Predictive preventive personalised medicine; Flammer syndrome; Breast cancer